Biographies of Scale - Kerry Duff (Disability Studies Quarterly, 2005)
The diverse collection of memoirs, lives, and autobiographies of those who exhibited as freaks in the late 18th and 19th century has often been neglected by scholars or treated as simply source material that describes the way in which these individuals were exhibited. By viewing these texts as performances of subjectivity, this essay considers both the complications that arise in the attempt to construct subjectivity and the rhetorical strategies deployed to negotiate them. The analysis will focus on the narratives of four individuals who exhibited as "midgets" in this period.
Keywords: memoirs; freaks; little people; Boruwlaski; Lavinia Warren Magri (Mrs. Tom Thumb)